Sea level rise simulation at Major Towns of East Coast of Peninsular Malaysia - Isfarita Ismail; Mohd Lokman Husain; Ejria Saleh; Mohamed Shawal M. Muslim (Universiti Teknologi Malaysia, 2024)
Global warming is caused by greenhouse gases resulting from natural causes and human activities. This event causes the sea level rise (SLR). The effects of SLR are the submerging of an area, saltwater intrusion, erosion, and the destruction of infrastructure and marine ecosystems. The objectives of this study are to identify the year when the sea water level rises 1 m, 2 m, and 3 m and to estimate inundated areas that are affected by floods at different sea water level scenarios at major towns of East Coast Peninsular Malaysia. The major cities selected are Kota Bharu, Kuala Terengganu, Kuantan, and Kota Tinggi, with a study site area of 96 km2 , 38 km2 , 16 km2, and 10 km2 , respectively. Study site selection is based on the high concentration of socioeconomic (quality of life, economic value, and infrastructure). The SLR of 1 m, 2 m, and 3 m was based on tidal data and IFSAR data for the SLR simulation. The data collected were analyzed using ERDAS 2011 and ArcGIS software. Based on the 1 m to 3 m SLR, the water level is predicted to occur from 2319 to 2374 for all study areas. Results indicate that Kota Bharu is the most affected by the 1, 2, and 3 m SLR, with an inundation area of 15%, 37%, and 60% of its total study area. For 1 m SLR, just 5% of the total study area will be inundated in Kuala Terengganu, but this will increase to 51% when the water level rises to 3 m. Kuantan and Kota Tinggi are located on higher ground, where an increase in seawater level to 3 m will affect about 40% of the study area. Other factors related to extreme events or/and human activities would be accelerating sea-level rise to severe impacts on low-lying over a short period. However, information on SLR projection at the local level is indeed part of the future coastal management and town development. Adaptation options and flood mitigation for the most affected area should be considered to minimize the impact of SLR.